Mediterranean crockery for honey of neolithic - early bronze period - Триколенко, О. В. (Proceedings of National Aviation University, 2003)
In the article is proved existence of the special dinner, ceremonial and ritual crockery for honey in Aegean world and in Eastern European cultures of essential Mediterranean influence during the time of Neolithic - Early Bronze